Atomic force microscopy to study molecular mechanisms of amyloid fibril formation and toxicity in Alzheimer's disease. (May 2014) - Drolle, Elizabeth; Hane, Francis; Lee, Brenda; Leonenko, Zoya
Abstract Alzheimer's disease (AD) is a devastating neurodegenerative disease characterized by dementia and memory loss for which no cure or effective prevention is currently available. Neurodegeneration in AD is linked to formation of amyloid plaques found in brain tissues of Alzheimer's patients during post-mortem examination. Amyloid plaques are composed of amyloid fibrils and small oligomers – insoluble protein aggregates. Although amyloid plaques are found on the neuronal cell surfaces, the mechanism of amyloid toxicity is still not well understood. Currently, it is believed that the cytotoxicity is a result of the nonspecific interaction of small soluble amyloid oligomers (rather than longer fibrils) with the plasma membrane. In recent years, nanotechnology has contributed significantly to understanding the structure and function of lipid membranes and to the study of the molecular mechanisms of membrane-associated diseases. We review the current state of research, including applications of the latest nanotechnology approaches, on the interaction of lipid membranes with the amyloid-β (Aβ) peptide in relation to amyloid toxicity. We discuss the interactions of Aβ with model lipid membranes with a focus to demonstrate that composition, charge and phase of the lipid membrane, as well as lipid domains and rafts, affect the binding of Aβ to the membrane and contribute to toxicity. Understanding the role of the lipid membrane in AD at the nanoscale and molecular level will contribute to the understanding of the molecular mechanism of amyloid toxicity and may aid into the development of novel preventive strategies to combat AD.